When to stop: Understanding the landscape of extreme-duration cardiopulmonary resuscitation practices among pediatricians in Sudan - Mohammed Abdulrahman Alhassan (PLoS ONE, 2025)
Background Pediatric cardiopulmonary resuscitation (CPR) is a life-saving intervention, but its effectiveness in extreme durations remains debated. This study aimed to explore the frequency and decision-making regarding prolonged CPR (PCPR) practices in hospitalized Sudanese children. Methods A web-based cross-sectional survey was conducted among pediatricians and pediatric trainees in Sudan. The survey investigated their experience with prolonged, ultra-prolonged, and extreme-duration CPR and factors influencing termination decisions. Results Ninety-six Sudanese pediatricians and trainees responded to the survey, reporting varied experiences with prolonged CPR durations: over half (51%) and 81% of respondents reported encountering extreme-duration (> 12 hours) and ultra-prolonged (> 2 hours) CPR at least once, respectively. Around 5% and 1% reported to have encountered CPR durations of 48–72 hours and more than 72 hours, respectively, while 18% reported a 12–14-hour as their record high CPR duration. Four participants reported encountering extreme-duration (> 12 hours) CPR more than 15 times. Respondents most frequently (41%) cited the absence of a pulse and heartbeat as the primary factor for terminating CPR. A vast majority acknowledged ethical considerations (84%) and a lack of clear protocols (83%) as a barrier to terminating PCPR. Thematic analysis of an open question revealed a critical need for a standardized protocol addressing PCPR, enhanced CPR training, and better post-resuscitation support. Conclusions This study revealed a relatively high frequency of extended-duration CPR in Sudanese pediatric settings. Termination decisions focused on cardiac activity becoming clinically undetectable rather than brain death signs or specific cutoff CPR durations. The absence of a clear protocol on when to terminate CPR seems to contribute the most to this phenomenon. Further research on patient outcomes after prolonged CPR in this context is warranted.